2018
DOI: 10.1159/000493802
|View full text |Cite
|
Sign up to set email alerts
|

An Animal Model for Wheat Allergy Skin Sensitisation: A Comparative Study in Naive versus Tolerant Brown Norway Rats

Abstract: Background: Allergic sensitisation to foods may occur in infancy without prior oral exposure to the offending food, leading to the assumption that food allergy sensitisation may occur through the skin. Concerns have been raised regarding the safety of use of personal care products containing hydrolysed wheat proteins, since these products have been shown to induce allergy through the skin, and even cause an abrogation of an already established oral tolerance. Objective: To establish an animal model for food al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 40 publications
(46 reference statements)
2
37
0
Order By: Relevance
“…Food allergy refers to a hypersensitivity disorder in which the immune system abnormally reacts to non-infectious environmental substances ( Galli et al., 2008 ), often induces a series of allergic disease complications, such as urticaria, asthma, and diarrhea, which could seriously affect quality of life ( Ballegaard et al., 2019 ). It has been recognized by the World Health Organization (WHO) as a major global food safety issue ( Wang et al., 2019 ) and seriously affected about as many as 10% of children globally ( Abrams et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Food allergy refers to a hypersensitivity disorder in which the immune system abnormally reacts to non-infectious environmental substances ( Galli et al., 2008 ), often induces a series of allergic disease complications, such as urticaria, asthma, and diarrhea, which could seriously affect quality of life ( Ballegaard et al., 2019 ). It has been recognized by the World Health Organization (WHO) as a major global food safety issue ( Wang et al., 2019 ) and seriously affected about as many as 10% of children globally ( Abrams et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The possible influence of tolerance to wheat was not discussed in that paper. A study by Ballegaard [23] sheds light on the influence of tolerance on sensitization via the skin. BN rats that were either naïve or tolerant to gluten were sensitized on slightly damaged skin with G or AHG.…”
Section: Plos Onementioning
confidence: 99%
“…Using a skin sensitization method, Ballegaard et al (2019) studied the allergenicity of native gluten vs. AHG in wheat-tolerant mice fed with wheat diet vs. naïve mice that had been on a wheat-free diet [48]. They found that in naïve rats that were not wheat-tolerant, both glutens elicited allergenic responses.…”
Section: Insights In To the Molecular Mechanisms Of Wheat Allergenmentioning
confidence: 99%
“…However, animal models can be used to study this critical issue. Currently, most animal models have used intraperitoneal (IP) injections in sensitization with the exception of one mouse and one rat model, where skin sensitization was used, and one rat model, where oral sensitization was studied [38,47,48] (Table 5). The mouse models used injections to elicit anaphylaxis.…”
Section: Insights In To the Molecular Mechanisms Of Wheat Allergenmentioning
confidence: 99%
See 1 more Smart Citation